基于线性二次型的刚柔耦合挖掘机机械臂轨迹追踪与振动控制 - 王猛 (Jixie chuandong)
For the problems of excavator manipulator trajectory tracking during operation and vibration control,the rigid-flexible coupling nonlinear dynamics model of excavator manipulator is established,the decoupling of two parts of joint angle variables and the elastic variables in the model is carried out,the excavator manipulator trajectory tracking and residual vibration suppression is calculated,the numerical verification of establishing related model is carried out according to the calculation data.The results show that excavator rigid-flexible coupling manipulator trajectory tracking control method is effective,linear quadratics optimal control method by the residual vibration of mechanical systems excavator elastic deformation caused by the flexible manipulator has played a significant inhibitory effect.